1987
DOI: 10.1080/09553008714550711
|View full text |Cite
|
Sign up to set email alerts
|

Rejoining of Double Strand Breaks in Normal Human and Ataxia-telangiectasia Fibroblasts after Exposure to60Co γ-rays,241Am α-particles or Bleomycin

Abstract: The rejoining of DNA double strand breaks (dsb) induced by 60Co gamma-rays, 241Am alpha-particles or bleomycin was measured by neutral filter elution. In agreement with their colony-forming ability, ataxia-telangiectasia cells (AT2BE) and normal fibroblasts exhibited similar dsb rejoining capacity following alpha-irradiation, but showed marked differences in the rejoining kinetics of dsb induced by gamma-rays or bleomycin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(24 citation statements)
references
References 20 publications
2
22
0
Order By: Relevance
“…4,6,7 Although earlier attempts failed to reveal any significant defect in double-strand break (DSBs) joining at short times after irradiation, Cornforth and Bedford 8 demonstrated the presence of residual chromosomal breaks in DNA from A-T cells post-irradiation using the premature chromosome condensation assay. Further support for a defect in DSB rejoining in A-T was provided by Coquerelle et al,9 who demonstrated that rejoining of radiation-induced DSBs was slower in A-T fibroblasts than in controls. Consistent with this, it was revealed that the overall extent of repair of breaks did not exceed 90% of control cells.…”
Section: A-t and Radiation Sensitivitymentioning
confidence: 98%
“…4,6,7 Although earlier attempts failed to reveal any significant defect in double-strand break (DSBs) joining at short times after irradiation, Cornforth and Bedford 8 demonstrated the presence of residual chromosomal breaks in DNA from A-T cells post-irradiation using the premature chromosome condensation assay. Further support for a defect in DSB rejoining in A-T was provided by Coquerelle et al,9 who demonstrated that rejoining of radiation-induced DSBs was slower in A-T fibroblasts than in controls. Consistent with this, it was revealed that the overall extent of repair of breaks did not exceed 90% of control cells.…”
Section: A-t and Radiation Sensitivitymentioning
confidence: 98%
“…Low repair fidelity and radioresistant DNA synthesis are both reported features of A-T (Cox et al, 1986;Debenham et al, 1988a;Painter, 1981). A-T cells have no defect in dsb rejoining (Lehmann, 1982) with one reported exception (Coquerelle et al, 1987).In a previous report (McMillan & Holmes, 1991), the initial DNA damage, measured by neutral filter elution, was found to be the same in clone S40b and the parent line, MGH-Ul. To investigate the possibility of a repair defect in S40b we have now looked at DNA repair under two broad headings: (1) the rate and extent of dsb rejoining (2) repair fidelity.…”
mentioning
confidence: 91%
“…Low repair fidelity and radioresistant DNA synthesis are both reported features of A-T (Cox et al, 1986;Debenham et al, 1988a;Painter, 1981). A-T cells have no defect in dsb rejoining (Lehmann, 1982) with one reported exception (Coquerelle et al, 1987).…”
mentioning
confidence: 99%
“…The exact cause of the radiosensitivity in A-T cells remains unknown but there is evidence that the rejoining of g-radiation-induced double strand breaks is slower in A-T ®broblasts (Coquerelle et al, 1987). Other reports demonstrate the continuing presence of residual double-strand breaks in DNA in A-T cells at 24 ± 72 h post-irradiation (Cornforth and Bedford, 1985;Foray et al, 1997).…”
Section: Introductionmentioning
confidence: 99%